INTEGRASI SISTEM DIGITALISASI DAN ANALYSIS LAPANGAN DALAM PERENCANAAN PENGEMBANGAN DAERAH: EVALUASI KEMAMPUAN LAHAN MILIK SWASTA - Melinda R.S. Moata; Oskar Kollo; Yofris Puay; Yos Rhuma; Charles Tlonaen; Zakharias Duka (Partner, 2018)
Utiliztion of dryland and bareground in urban area is an opportunity as well challenge. One of the importat factors for land uses decician is evaluation of land capability and suitability. In agriculture, one of the causing of land degradation is unsuitable land uses. Therefore, PT. Angkasa Pura El Tari Int. Airport Kupang colaburated with academitients to conduct land evaluation at one of unmanaged land in urban area.This survey was conducted on the land of 10,078 Ha at Lasiana, Kupang city, East NusaTenggara Timur. The methods comprised of stated of aims, planning (overlay maps from ArcGIS 10,3), ground survey, data analysis (erosion prediction by USLE (Universal Soil Loss Equation) method, data compilation and presentation. The results provided two land units that considered in class III of land capability with limiting factors (soil depth, erosion level,soil fertility, drainase, and stony). Therefore there are some recommendations for land management, such as increasing soil depth by adding some soils,growing annual crops, forest trees, nursery, grassing combination with countering and terrasering on the land with high slope, tillage system, and organic matter amandement. Due to the location is in the urban areas (Kupang city), it is suggested to apply urban forest or urban farming development using multifunctional land uses approach, functioning for agriculture, natural conservation, social activities, education and agrotourism.